2016
DOI: 10.5056/jnm15157
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical Course of Post-infectious Irritable Bowel Syndrome After Shigellosis: A 10-year Follow-up Study

Abstract: Background/AimsA limited number of studies are available regarding the long-term natural history of post-infectious irritable bowel syndrome (PI-IBS). We aimed to investigate the long-term clinical course of PI-IBS. MethodsA prospective cohort study was conducted from a 2001 shigellosis outbreak in a Korean hospital with about 2000 employees. A cohort of 124 hospital employees who were infected by Shigella sonnei due to contaminated food in the cafeteria, and 105 sex-and age-matched, non-infected, controls wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Overall, the rates of PI-IBS were highest after protozoal/parasitic IE, 1113, 46 followed by bacterial IE, 4, 5, 17, 2015, 31, 34, 35, 3844, 47, 5055, 57, 58 and lowest rates were seen with viral IE 710 (Figure 2). Summary estimate shows significant heterogeneity (I 2 ≥95%) among studies.…”
Section: Resultsmentioning
confidence: 97%
“…Overall, the rates of PI-IBS were highest after protozoal/parasitic IE, 1113, 46 followed by bacterial IE, 4, 5, 17, 2015, 31, 34, 35, 3844, 47, 5055, 57, 58 and lowest rates were seen with viral IE 710 (Figure 2). Summary estimate shows significant heterogeneity (I 2 ≥95%) among studies.…”
Section: Resultsmentioning
confidence: 97%
“…A recently published 10-year follow-up study found a significant association between exposure to shigellosis and PI-IBS 1 and 3 years after the infection, but no significant association 5, 8, or 10 years later. 7 The Walkerton outbreak had a follow-up time of 8 years, and found that exposure to a mixture of bacterial pathogens was associated with PI-IBS 8 years after exposure, with a prevalence of PI-IBS among exposed of 15.4%. 6 Previous research has suggested that bacterial pathogens cause longer lasting symptoms of PI-IBS than viral pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Postinfectious IBS (PI-IBS) has been described following outbreaks, among travelers returning from abroad, or as sporadic cases. [5][6][7][8][9][10] The rate of recovery from PI-IBS varies between studies, and bacterial infections seem to be associated with more prolonged symptoms than viral infections. 10 One study after an outbreak of bacterial dysentery reported that IBS was associated with exposure up to 8 years after the acute infection.…”
mentioning
confidence: 99%
See 2 more Smart Citations